Level of acquisition of consumer goods: a rasch analysis - Ibrahim, Zin; Abdul Rahman, Zanariah; Othman, Akmal Aini (Institut Pengurusan Penyelidikan, Pembangunan & Pengkomersilan, 2005)
Marketing research indicates that consumers acquire consumer goods in a pattern. One method of investigating this pattern is Guttman scaling; however, it is too restrictive as it excludes responses that do not follow the Guttman pattern. On the other hand, the Rasch model accepts all patterns of responses. The model expresses the probability of a consumer acquiring a consumer good by using the ability of the consumer and the difficulty of market penetration of the consumer good. To create a measuring instrument for consumer acquisition, a survey asked 500 respondents from Kluang which of 22 consumer items they had acquired. Winsteps, a computer program using the Rasch model, investigated the fit between the observed data and the Rasch model. The fit statistics showed that 17 items followed the Rasch model to form a reliable measuring instrument of acquisition. The items, in increasing order of difficulty of market penetration, are: blender, radio, rice cooker, VCD, toaster, TV (at least 29 inches), vacuum cleaner, computer, electric kettle, water heater, hairdryer, stereo, microwave, PlayStation, air conditioner, ASTRO, and VCR. The results show that the acquisition levels of the household increase with the income of the household.